2010
DOI: 10.1128/ec.00077-10
|View full text |Cite
|
Sign up to set email alerts
|

Two Components of a velvet -Like Complex Control Hyphal Morphogenesis, Conidiophore Development, and Penicillin Biosynthesis in Penicillium chrysogenum

Abstract: Penicillium chrysogenum is the industrial producer of the antibiotic penicillin, whose biosynthetic regulation is barely understood. Here, we provide a functional analysis of two major homologues of the velvet complex in P. chrysogenum, which we have named P. chrysogenum velA (PcvelA) and PclaeA. Data from array analysis using a ⌬PcvelA deletion strain indicate a significant role of PcVelA on the expression of biosynthesis and developmental genes, including PclaeA. Northern hybridization and high-performance l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
207
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 146 publications
(233 citation statements)
references
References 74 publications
22
207
4
Order By: Relevance
“…We have recently described PcVelA, a core component of the velvet complex, which is associated with PcLaeA, a regulator of secondary metabolism in P. chrysogenum (26). The PcVelA sequence from P. chrysogenum together with sequences homologous to velvet subunits from different Aspergilli and Neosartoria species served as sources to identify genes encoding velvet proteins PcVelB, PcVelC, and PcVosA in the P. chrysogenum genome (35).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently described PcVelA, a core component of the velvet complex, which is associated with PcLaeA, a regulator of secondary metabolism in P. chrysogenum (26). The PcVelA sequence from P. chrysogenum together with sequences homologous to velvet subunits from different Aspergilli and Neosartoria species served as sources to identify genes encoding velvet proteins PcVelB, PcVelC, and PcVosA in the P. chrysogenum genome (35).…”
Section: Resultsmentioning
confidence: 99%
“…Sequences representing conserved motifs were manually extracted from alignments edited with GeneDoc (44). Microarray analysis was performed as described previously by Hoff et al (26). The microarray data used in this study are available from the GSE18585 series at the NCBI Gene Expression Omnibus (GEO) repository (26,45).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a major finding because MAT genes have previously been primarily known for their role in determining sexual identity, as well as for other aspects of sexual development (19). We had previously observed that hyphal morphology, and consequently pellet formation, in P. chrysogenum is dependent on a wide range of factors (44). Hyphal morphology in submerged fermentations is a highly important feature of production strains in large-scale fermenters because this can influence productivity as a result of oxygen depletion and nutritional gradients (45).…”
Section: Discussionmentioning
confidence: 97%
“…Despite a high level of structural conservation among filamentous ascomycetes, velvet orthologues have divergent roles depending on the fungal species. In N. crassa, A. nidulans and Penicillium chrysogenum, deletion of veA orthologues leads to an increase in light-independent conidial formation, whereas deletion in Aspergillus parasiticus and Aspergillus fumigatus results in a general decrease in conidiation, which is dependent on the nutritional composition of the medium (Bayram et al, 2008;Calvo et al, 2004;Hoff et al, 2010, Krappmann et al, 2005Mooney & Yager, 1990). A reduction in conidiation has also been observed in Aspergillus flavus and Fusarium fujikuroi veA orthologue deletion mutants (Amaike & Keller, 2009;Wiemann et al, 2010).…”
Section: Global Regulation By the Velvet Proteinmentioning
confidence: 95%